2015
DOI: 10.1128/jb.02533-14
|View full text |Cite
|
Sign up to set email alerts
|

Basal Body Structures Differentially Affect Transcription of RpoN- and FliA-Dependent Flagellar Genes in Helicobacter pylori

Abstract: Flagellar biogenesis in Helicobacter pylori is regulated by a transcriptional hierarchy governed by three sigma factors, RpoD ( 80 ), RpoN ( 54 ), and FliA ( 28 ), that temporally coordinates gene expression with the assembly of the flagellum. Previous studies showed that loss of flagellar protein export apparatus components inhibits transcription of flagellar genes. The FlgS/FlgR two-component system activates transcription of RpoN-dependent genes though an unknown mechanism. To understand better the extent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 51 publications
3
18
0
Order By: Relevance
“…Additionally, we found that V. cholerae FliF mutants that likely fail to form an MS ring were defective in FlrBC TCS activity. These findings are similar to our previous studies in C. jejuni and what others have reported in H. pylori (32,40,41,43). Furthermore, we accumulated evidence that for at least P. aeruginosa (and possibly V. cholerae), more domains of the FliG rotor were required for flagellum-associated TCS activity than in C. jejuni.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Additionally, we found that V. cholerae FliF mutants that likely fail to form an MS ring were defective in FlrBC TCS activity. These findings are similar to our previous studies in C. jejuni and what others have reported in H. pylori (32,40,41,43). Furthermore, we accumulated evidence that for at least P. aeruginosa (and possibly V. cholerae), more domains of the FliG rotor were required for flagellum-associated TCS activity than in C. jejuni.…”
Section: Discussionsupporting
confidence: 92%
“…Detection of this regulatory checkpoint by an orthologous FlgSR TCS also may occur in Helicobacter pylori, a lophotrichous epsilonproteobacterium closely related to C. jejuni, for transcription of 54 -dependent rod and hook genes (34)(35)(36)(37). Genetic analyses indicate that H. pylori FlgSR TCS activity for rod and hook gene transcription is also dependent on fT3SS, MS ring, and C ring proteins, suggesting that this TCS in H. pylori also senses the formation of a competent fT3SS (38)(39)(40)(41)(42)(43).…”
mentioning
confidence: 97%
“…H. pylori also appears to have different requirements of C-ring proteins for flagellar assembly from those to C. jejuni. H. pylori fliM and fliY mutants are severely defective for flagellar biogenesis, but a fliN mutant is much less so; all of these H. pylori mutants are generally less flagellated than are the respective C. jejuni mutants (56,57,88). Our work combined with this analysis in H. pylori, a closely related epsilonproteobacterium, demonstrate that flagellar motors are composed of different components across bacterial species, which result in motors with different assemblies of substructures, alteration of motor output for propulsion, and roles outside flagellar motility.…”
Section: Discussionmentioning
confidence: 99%
“…The flagellum is structurally composed of the basal body, hook, and filament (Ran Kim and Haeng Rhee, 2003; Hirano et al, 2009; Evans et al, 2014; Gao et al, 2014; Tsang and Hoover, 2015). The basal body serves as a rotation axis and consists of the MS-ring, C-ring, PL-ring, and rod.…”
Section: Discussionmentioning
confidence: 99%